2016
DOI: 10.1111/iej.12611
|View full text |Cite
|
Sign up to set email alerts
|

Pulp sensibility and vitality tests for diagnosing pulpal health in permanent teeth: a critical review

Abstract: The aim of this review was to critically appraise the literature related to pulp vitality and sensibility testing in order to determine the diagnostic accuracy of pulp tests with reference to a gold standard or control group. Implications of the results for research and clinical practice are also explored. The MEDLINE (Ovid), MEDLINE (PubMed), Embase and Cochrane databases were searched for English-language clinical trials in humans in which in vivo studies were designed to evaluate or compare the accuracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 28 publications
(118 reference statements)
5
104
1
8
Order By: Relevance
“…In one of the first studies demonstrating the utility of pulse oximetry in dentistry, Schnettler and Wallace showed that a pulse oximeter could detect pulse rate and oxygen saturation for vital teeth and not for root canal treated teeth. This work has now been replicated by several groups 20, 65, 66, 67, 69. Interestingly, Gopikishna showed that normal oxygen saturation in human permanent teeth was lower than systemic blood measured in fingers, 75% to 85% versus 98%, respectively 70.…”
Section: Mechanisms Of Orofacial Painmentioning
confidence: 78%
See 2 more Smart Citations
“…In one of the first studies demonstrating the utility of pulse oximetry in dentistry, Schnettler and Wallace showed that a pulse oximeter could detect pulse rate and oxygen saturation for vital teeth and not for root canal treated teeth. This work has now been replicated by several groups 20, 65, 66, 67, 69. Interestingly, Gopikishna showed that normal oxygen saturation in human permanent teeth was lower than systemic blood measured in fingers, 75% to 85% versus 98%, respectively 70.…”
Section: Mechanisms Of Orofacial Painmentioning
confidence: 78%
“…Modern pulse oximeters now provide an inexpensive and efficient method to measure blood oxygenation. Pulse oximetry can detect oxygen saturation levels of the pulp tissue based on spectrophotometry using a light source (wavelengths 760 and 850 nm) 65, 66, 67, 68. In one of the first studies demonstrating the utility of pulse oximetry in dentistry, Schnettler and Wallace showed that a pulse oximeter could detect pulse rate and oxygen saturation for vital teeth and not for root canal treated teeth.…”
Section: Mechanisms Of Orofacial Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulp diagnosis is complicated by the loss of sensibility caused by the traumatic injury and the difficulty of pulp sensibility tests in children. 3,4 Pulp vitality tests, such as using laser Doppler flowmetry (LDF), were shown to be more accurate than pulp sensibility tests, [5][6][7] especially after traumatic injuries. In case reports or case series, [8][9][10] LDF showed the onset of vitality signals in luxated teeth much sooner than sensibility | 325 FOUAD testing.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the pulp's response to stimuli is crucial in providing a diagnosis and choosing the proper treatment . In a clinical examination, subjective tests of the patient's response to thermal stimuli (heat and cold), mechanical procedures (dentin drilling) and electric tests are used . The pulp of the tooth is a highly innervated tissue rich in vessels.…”
Section: Introductionmentioning
confidence: 99%